Drivers of tax avoidance: A literature review approach - Kasir, Kasir; Djajadikerta, Hamfri; Maratno, Sylvia Fettry Elvira (Edelweiss Applied Science and Technology, 2025)
Tax Avoidance is a deliberate action by taxpayers/companies to reduce their tax obligations either legally or illegally. Because the boundaries between legal and illegal actions are not clear, the legality of an action in terms of corporate tax is determined by an authoritative body, so that it can see what is allowed and what is not. The purpose of this study was to determine the distribution of articles on tax avoidance based on the names of publishers and their years, countries, research topics, measurements used and what factors can encourage companies to avoid tax. This study uses a qualitative method based on literature studies. Data were obtained from articles published through the emerald.com, elseiver.com, springer.com and other websites by filtering research titles and using the keyword "Tax Avoidance" from 2012 to 2021 and above. Based on the mapping and process of selecting articles, the author took 45 articles. The results of the study indicate that the distribution of articles based on research topics is about corporate governance, based on measurement is ETR, based on driving factors are corporate governance factors, social responsibility and corporate performance. The practical implication is that this study can be used as a reference for conducting further research based on the mapping results.